1994
DOI: 10.1901/jaba.1994.27-737
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a High‐probability Request Sequence With Varied Interprompt Times in a Preschool Setting

Abstract: An intervention for noncompliance consisting of a series of requests promoting a high probability of compliance followed either 5 s or 20 s later by a request with a low probability of compliance was implemented with a preschool child with autism. Results indicated that applications of the request sequence with a shorter interprompt time resulted in higher rates of compliance, and longer interprompt times resulted in near-baseline rates of compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…Treatment consisted of presenting a rapid sequence of high-probability (high-p) instructions immediately preceding a low-probability (low-p) instruction with which the client was normally noncompliant. This article and several replications of the high-p treatment have shown that the intervention can increase compliance to clinically acceptable levels with individuals with normal development and individuals with mental retardation (Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Davis, Brady, Williams, & Hamilton, 1992;Ducharme & Worling, 1994;Harchik & Putzier, 1990;Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Houlihan, Jacobson, & Brandon, 1994;Mace & Belfiore, 1990;Singer, Singer, & Horner, 1987).…”
mentioning
confidence: 93%
“…Treatment consisted of presenting a rapid sequence of high-probability (high-p) instructions immediately preceding a low-probability (low-p) instruction with which the client was normally noncompliant. This article and several replications of the high-p treatment have shown that the intervention can increase compliance to clinically acceptable levels with individuals with normal development and individuals with mental retardation (Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Davis, Brady, Williams, & Hamilton, 1992;Ducharme & Worling, 1994;Harchik & Putzier, 1990;Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Houlihan, Jacobson, & Brandon, 1994;Mace & Belfiore, 1990;Singer, Singer, & Horner, 1987).…”
mentioning
confidence: 93%
“…High-p instruction sequences involve the rapid presentation of three instructions with which an individual is likely to comply immediately preceding an instruction with a low probability of compliance. This procedure has been used successfully to increase compliance and decrease aberrant behavior in adults with developmental disabilities (e.g., Mace & Belfiore, 1990;Zarcone, Iwata, Mazaleski, & Smith, 1994) as well as children and youth with severe handicaps (e.g., Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Ducharme & Worling, 1994;Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Houlihan, Jacobson, & Brandon, 1994;Kennedy, Itkonen, & Lindquist, 1995;Singer et al, 1987).…”
mentioning
confidence: 99%
“…In treating a developmentally disabled adult, Mace et al demonstrated that by issuing a sequence of three to five commands the subject was likely to comply with (high-p commands) prior to issuing a command s/he was unlikely to comply with (low-p commands), compliance to the low-p commands could be dramatically increased. This strategy has been successfully replicated across a variety of populations including autistic children (Davis, Brady, Williams, & Hamilton, 1992;Houlihan, Jacobson, & Brandon, 1994), individuals with selfinjurious behaviors (Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Zarcone, Iwata, Mazaleski, & Smith, 1994), children with social skills deficits (Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Kennedy, Itkonen, & Lindquist, 1995), and individuals who are being noncompliant with specific medical regimens (Harchik & Putzier, 1990).…”
Section: Out Of the Operant Chamber And Into The Classroommentioning
confidence: 99%